2020
DOI: 10.1097/prs.0000000000007274
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Flap Closure following Complex Spine Surgery: A Decade of Experience

Abstract: Background: Advances in surgical technology and adjuvant therapies along with an aging and increasingly morbid U.S. population have led to an increase in complex spine surgery. With this increase comes an elevated risk of complications, including those related to the surgical wound, with some studies demonstrating wound complication incidences approaching 45 percent. The authors hypothesize that immediate muscle flap closure improves outcomes in high-risk patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Prior published studies have suggested stratifying patients' risk factors and offering plastic surgery reconstruction for those in higher risk categories as a potential management strategy, given that not every patient who undergoes spine surgery may receive additional benefit from plastic surgery involvement 11,28 . Wright et al 28 reviewed a single institution's experience with muscle flap closure for spine surgery and found that the highest-risk patients, such as those with a history of radiotherapy and prior spine surgery, had increased major wound complications, concluding that these patients would benefit from plastic surgery closure. Another study found that history of radiotherapy, smoking, and diabetes are associated with developing complex spinal wounds and that prophylactic flap coverage helped to lower the incidence of wound complications 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior published studies have suggested stratifying patients' risk factors and offering plastic surgery reconstruction for those in higher risk categories as a potential management strategy, given that not every patient who undergoes spine surgery may receive additional benefit from plastic surgery involvement 11,28 . Wright et al 28 reviewed a single institution's experience with muscle flap closure for spine surgery and found that the highest-risk patients, such as those with a history of radiotherapy and prior spine surgery, had increased major wound complications, concluding that these patients would benefit from plastic surgery closure. Another study found that history of radiotherapy, smoking, and diabetes are associated with developing complex spinal wounds and that prophylactic flap coverage helped to lower the incidence of wound complications 13 .…”
Section: Discussionmentioning
confidence: 99%
“…PMC for spinal wounds have been described in the literature. In 2022, Wright et al 15 described a series of 301 patients (76% having comorbidities) undergoing muscle flap closure with a major wound complication rate of 20%. In 2015, Cohen et al 16 described 102 PMCs reconstructions in 96 patients (86% classified as high risk) with a markedly low major wound complication rate of 6% and overall wound complication rate of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Revision surgery was cited as a common indication to perform a flap closure at that study institution 12 . Wright et al 17 reviewed 300 spines fused on average of 4.6 levels and closed by a single plastic surgeon using local muscle flaps, and they identified prior spine surgery both as the most common indication of muscle flap closure and as a major risk factor for wound complications.…”
Section: Discussionmentioning
confidence: 99%